2015
DOI: 10.1007/s10162-015-0509-9
|View full text |Cite
|
Sign up to set email alerts
|

The Olivocochlear Reflex Strength and Cochlear Sensitivity are Independently Modulated by Auditory Cortex Microstimulation

Abstract: In mammals, efferent projections to the cochlear receptor are constituted by olivocochlear (OC) fibers that originate in the superior olivary complex. Medial and lateral OC neurons make synapses with outer hair cells and with auditory nerve fibers, respectively. In addition to the OC system, there are also descending projections from the auditory cortex that are directed towards the thalamus, inferior colliculus, cochlear nucleus, and superior olivary complex. Olivocochlear function can be assessed by measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 58 publications
2
47
2
4
Order By: Relevance
“…In the current study we show power modulations of OOA in frequencies that in the cortical literature have been repeatedly reported to be related to various attentional task demands Fries et al, 2001;Klimesch, 2012;Wutz et al, 2018). Electrical stimulation of the auditory cortex in bats and chinchillas shows that cochlear responses can be modulated in a frequency specific manner (Dragicevic et al, 2015;León et al, 2012;Xiao & Suga, 2002). The current results imply that the modulation of cochlear low-frequency oscillatory power putatively is driven by top-down attentional processes (note that the frequency is unchanged).…”
Section: Discussionsupporting
confidence: 77%
“…In the current study we show power modulations of OOA in frequencies that in the cortical literature have been repeatedly reported to be related to various attentional task demands Fries et al, 2001;Klimesch, 2012;Wutz et al, 2018). Electrical stimulation of the auditory cortex in bats and chinchillas shows that cochlear responses can be modulated in a frequency specific manner (Dragicevic et al, 2015;León et al, 2012;Xiao & Suga, 2002). The current results imply that the modulation of cochlear low-frequency oscillatory power putatively is driven by top-down attentional processes (note that the frequency is unchanged).…”
Section: Discussionsupporting
confidence: 77%
“…Efferent MOC fibers project to outer hair cells (OHCs) in the cochlea and activation of these fibers alters OHC activity, effectively reducing cochlear gain (reviews: Guinan, 2006Guinan, , 2018. Efferent MOC-fiber activity can be modulated in a 'topdown' manner: electric microstimulation or deactivation of the auditory cortex alters OHC activity as measured with cochlear microphonics or otoacoustic emissions (OAEs) (Perrot et al, 2006;Dragicevic et al, 2015;Terreros and Delano, 2015;Jager and Kossl, 2016). Similarly, changes in arousal or endogenous (interor intramodal) attention may lead to OHC-activity changes as measured with OAEs (Puel et al, 1988;Froehlich et al, 1990Froehlich et al, , 1993Giard et al, 1994;Ferber-Viart et al, 1995;Maison et al, 2001;de Boer and Thornton, 2007;Harkrider and Bowers, 2009;Smith et al, 2012;Srinivasan et al, 2012Srinivasan et al, , 2014Walsh et al, 2014Walsh et al, , 2015Wittekindt et al, 2014;Smith and Cone, 2015), although the existence and direction of these top-down attention effects are still debated (Picton et al, 1971;Avan and Bonfils, 1992;Michie et al, 1996;Beim et al, 2018Beim et al, , 2019Francis et al, 2018;Lopez-Poveda, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few physiological studies have assessed the corticofugal effects of auditory cortex manipulations on the most peripheral auditory structures, including, auditory nerve responses (León et al, 2012 ; Dragicevic et al, 2015 ), cochlear electrical responses (Xiao and Suga, 2002 ; León et al, 2012 ; Dragicevic et al, 2015 ) and otoacoustic emissions (OAE; Khalfa et al, 2001 ; Perrot et al, 2006 ). In a seminal work, Xiao and Suga ( 2002 ) demonstrated that the auditory cortex activity modulates the amplitude and frequency tuning of cochlear microphonics (CM) responses near the echolocalizing frequency of the mustached bat (61 kHz).…”
Section: Corticofugal Effects On Auditory-nerve and Cochlear Responsementioning
confidence: 99%